1998
DOI: 10.1002/(sici)1099-0488(199810)36:14<2643::aid-polb17>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Observations of crystallization and melting in poly(ethylene oxide)/poly(methyl methacrylate) blends by hot-stage atomic-force microscopy

Abstract: The binary blend of poly(ethylene oxide)/atactic poly(methyl methacrylate) is examined using hot‐stage atomic‐force microscopy (AFM) in conjunction with differential scanning calorimetry and optical microscopy. It was found possible to follow in real time the melting process, which reveals itself to be nonuniform. This effect is ascribed to the presence of lamellae having different thicknesses. The crystallization process of poly(ethylene oxide) from the miscible melt is also followed in real time by AFM, affo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
(44 reference statements)
0
35
0
Order By: Relevance
“…The AFM was fitted with a hot-stage to observe the quiescent crystallization in real-time. AFM studies of crystallization [70][71][72][73][74][75][76] have been reported, but none have focused on the quiescent crystallization of polyethylene-a-olefin copolymers. Because the melt is relatively ''sticky,'' hard tapping force was used to image the crystallization as it occurred.…”
Section: Resultsmentioning
confidence: 99%
“…The AFM was fitted with a hot-stage to observe the quiescent crystallization in real-time. AFM studies of crystallization [70][71][72][73][74][75][76] have been reported, but none have focused on the quiescent crystallization of polyethylene-a-olefin copolymers. Because the melt is relatively ''sticky,'' hard tapping force was used to image the crystallization as it occurred.…”
Section: Resultsmentioning
confidence: 99%
“…But, in an ultrathin or thin film, a constrained geometry system, the properties of polymer chains, such as crystallinity, chain packing and orientation, are different from the bulk state. Atomic force microscopy (AFM) studies of thin polymer films have visualized the growth [1][2][3][4][5][6][7][8] and melting [7,9] of crystalline lamellae in spherulites and the lamellar growth in shishkebab structures, [10,11] and also given rise to some controversial topics in the field of existing polymer crystallization theories. [3] Branched crystalline patterns different from spherulite have been observed in ultrathin polymer films.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic feature of PEO lamellae is their aggregation in a radial pattern. When formed this way, much larger structures (spherulites) typical for PEO crystallization from solutions or from molten polymers have been observed with optical polarizing microscopy because of their optical anisotropy 47, 48…”
Section: Resultsmentioning
confidence: 99%